Strategi Pembelajaran Pendidikan Agama Islam Berbasis Moderat Di Perguruan Tinggi Keagamaan Islam - Ahmad Sodikin (JURNAL PENDIDIKAN ISLAM AL I’TIBAR, 2019)
The rise of radicalism and terrorism in Indonesia which is done by some Muslims shows that educational institutions are less successful in forming moderate Muslims. Through educational institutions under the organization of moderate Islam, Muhammadiyah and Nahdlatul Ulama proved to be able to produce a generation of Moderate Muslims. This phenomenon is very interesting for the researcher to investigate more deeply about the Learning Strategies of Islamic Educational Learning in Forming Moderate Muslims (Multi-Case Studies at the University of Muhammadiyah Malang (UMM) and Malang Islamic University (UNISMA). The focus of study is Learning Strategis of Islamic education Learning for moderate Muslims. learning plan Islamic education consists of (1) making curriculum, (2) making syllabus, (3) making SAP (4) inner preparation from lecturers such as prayer Dhuha, tahajud, praying for students, practicing sholawat Nuril Anwar. followed by presentations and student discussions, lastly the lecturers present explanations related to the problems in the discussion. Fourth, the implications of PAI learning are embedded by some moderate thoughts on students and the entire academic community, the inherent shohihah aqidah and ahlussunnah wa al jamā'ah, and the absence of radical Islamic organizations in the university, and it is not permissible to cover faces for women.